Safety of autologous freshly expanded mesenchymal stromal cells for the treatment of graft-versus-host disease - Elizabeth Stenger; Cynthia R. Giver; Amelia Langston; Daniel Kota; Pankoj Kumar Das; Raghavan Chinnadurai; Jacques Galipeau; Edmund K. Waller; Muna Qayed (Frontiers in Immunology, 2022)
Despite the curative potential of hematopoietic cell transplantation (HCT) for hematologic malignancies, graft-versus-host disease (GVHD) remains a substantial cause of morbidity and mortality, particularly if treatment is refractory. Treatment with additional immunosuppression including steroids often leads to opportunistic infections and organ dysfunction. Novel therapies are greatly needed, specifically ones that lead to responses in treatment-refractory patients and are better tolerated. Mesenchymal stromal cells (MSCs) are non-hematopoietic tolerogenic cells present in normal bone marrow (BM), which can be expanded ex vivo to therapeutic doses. Their safety and efficacy have been assessed in inflammatory disorders including GVHD, but heterogeneity in clinical responses has led some to examine MSC manufacturing and administration procedures, which may impact in vivo efficacy. We hypothesized that autologous, early-passage, and culture-recovered (after freeze and thaw) MSCs would be safe and may have superior efficacy. In this phase I single-center trial, we assessed MSC safety and early efficacy of an escalating number of doses (2 × 106/kg doses; dose level 1, single dose; dose level 2, two weekly doses; dose level 3, four weekly doses) in patients aged ≥12 years with treatment-refractory acute or chronic GVHD. Eleven enrolled patients received some or all planned MSC infusions, with a median age at enrollment of 37 years. The most common primary HCT indication was leukemia, and the median time from HCT to first MSC infusion was 2.6 years. MSC infusion was well tolerated, with all severe adverse events expected and determined to be unlikely or definitely not related to the study. Thus, no dose-limiting toxicities occurred in the three dose levels. Three of four patients with acute GVHD (or overlap with acute features) had responses seen at any timepoint, ranging from partial to complete. In those with a chronic GVHD indication (n = 7), an overall response at 3 months was partial in five, stable in one, and progressive in one. No appreciable differences were seen between dose levels in peripheral blood lymphocyte subsets. In conclusion, autologous and culture-recovered MSCs were safe in the setting of refractory GVHD following HCT for hematologic malignancy, and clinical responses were most notable in patients with acute GVHD.